The Good Practices Catalogue of Participatory Urban Agriculture - Šmid Hribar, Mateja; Poljak Istenič, Saša; Kozina, Jani; Kumer, Peter (ZRC SAZU, Založba ZRC, 2018)
The Good Practices Catalogue of Participatory Urban Agriculture addresses some of the main challenges related to governance systems within the Danube Region that can be associated with the decreasing capacities of public authorities to incorporate a participatory approach into planning. It offers concrete lessons on how to enhance public services, promote active citizenship, reinforce public participation and contribute to the sustainability of cities by means of urban agriculture. It brings conceptualization and systematization of urban agriculture~analysis of political framework that supports participatory urban agriculture in the Danube Region~review of the role of urban agriculture in the EU-funded programmes and projects and of their relevance for the questions addressed by the AgriGo4Cities project~and presentation of selected good practices of participatory urban agriculture aiming to provide a know-how about designing successful participatory gardens. It addresses scholars and practitioners (civil society and decision-makers) interested in the fields of urban agriculture, participatory planning, social inclusion and sustainable development.